2018
DOI: 10.1111/1755-6724.13493
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Metamorphism and Provenance of the Metamorphic Basement of the Xiangshan Uranium Orefield, Jiangxi Province, China

Abstract: The origin, age and evolution of the Precambrian metamorphic basement of southern China provide useful insights into early crustal development. Here, we present new laser ablation–inductively coupled plasma–mass spectrometry (LA–ICP–MS) U–Pb age data for detrital zircons from five samples of the Precambrian metamorphic basement of the Xiangshan uranium orefield. Two of these samples, from the northern Xiangshan volcanic basin, yielded a total of 140 U–Pb ages that cluster within the Neoproterozoic (773–963 Ma;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Although their phylogenetic affinities and classifications are still to be solved, they have a great potential for dating late Neoprozerozoic to Early Paleozoic sedimentary rocks (Moldowan and Talyzina, 1998;Talyzina and Moczydlowska, 2000;Servais et al, 2004;Nowak et al, 2015;Yin, 1995), including low-grade clastic meta-sedimentary sequences (Montenari et al, 2000;Bian et al, 2001;Beccaletto et al, 2005). Organicwalled microfossils have previously been noted in the "Shenshan and Kuli formations" in the study area (DJMRJP, 1997;Ling et al, 2004;Guo et al, 2018), but no description has been provided.…”
Section: Samples and Methodsmentioning
confidence: 90%
See 3 more Smart Citations
“…Although their phylogenetic affinities and classifications are still to be solved, they have a great potential for dating late Neoprozerozoic to Early Paleozoic sedimentary rocks (Moldowan and Talyzina, 1998;Talyzina and Moczydlowska, 2000;Servais et al, 2004;Nowak et al, 2015;Yin, 1995), including low-grade clastic meta-sedimentary sequences (Montenari et al, 2000;Bian et al, 2001;Beccaletto et al, 2005). Organicwalled microfossils have previously been noted in the "Shenshan and Kuli formations" in the study area (DJMRJP, 1997;Ling et al, 2004;Guo et al, 2018), but no description has been provided.…”
Section: Samples and Methodsmentioning
confidence: 90%
“…770 Ma, based on the youngest peak ages. Guo et al (2018) reported U-Pb zircon ages of 773 ± 13 Ma and 767 ± 12 Ma from a turbidite in the Xiangshan area, about 10 km east of the study area (see also Yu et al, 2018). It should be noted that the youngest zircon ages obtained by Wang et al (2020) are ca.…”
Section: Confirmation Of the Shenshan Tectonic Mé Langementioning
confidence: 89%
See 2 more Smart Citations
“…4) (Li, 1999;Yao et al, 2014c), which were subsequently exposed at the surface. In the central JO, the initial collision and final assemblage of the Yangtze with the Cathaysia Block was constrained to between 830 and 810 Ma, respectively Guo et al, 2018).…”
Section: Stage 2: Amalgamation Of the Yangtze And Cathaysia Blocks Dumentioning
confidence: 99%